Irena's children : the extraordinary story of the woman who saved 2,500 children from the Warsaw ghetto - Mazzeo, Tilar J. (Gallery Books, 2016)
The "extraordinary and gripping account of Irena Sendler--the "female Oskar Schindler"--who took staggering risks to save 2,500 children from death and deportation in Nazi-occupied Poland during World War II"--Dust jacket.